Global Geopolitical Dynamics: Challenges and Opportunities For Indonesian Diplomacy - Achmad Nizar (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study examines the evolving global geopolitical landscape and its implications for Indonesia's diplomacy, focusing on economic, political, and security dimensions. The intensifying rivalry between the United States and China has reshaped global trade, investment flows, and regional security dynamics, posing both challenges and opportunities for Indonesia. Politically, Indonesia must navigate regional tensions, such as the South China Sea dispute, while reinforcing its leadership within ASEAN. Economically, global uncertainties stemming from the COVID-19 pandemic, supply chain disruptions, and energy crises necessitate a more proactive economic diplomacy strategy to attract investment and strengthen trade partnerships. In the security domain, emerging threats such as cyber warfare, climate change, and terrorism underscore the urgency of Indonesia's active engagement in international security frameworks. This research employs a qualitative methodology, using a literature review of policy documents, academic publications, and international reports to assess Indonesia's current diplomatic efforts and their effectiveness in addressing the changing global order. The findings indicate that Indonesia faces three primary challenges: maintaining strategic neutrality in great-power competition, ensuring regional stability, and enhancing economic resilience. Strengthening multilateral diplomatic engagements and leveraging Indonesia's position within regional and international organizations is essential for the country to navigate these geopolitical transformations effectively and safeguard its national interests in an increasingly complex global environment.